PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan PT. KAO di Kota Semarang) - Yuniar, Bintang; Farida, Naili; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
This study is about the Influence of Motivation, Work Environment and Work Discipline on Employee Performance (Case Study On Employee PT. KAO Semarang). This research was made possible thanks to employee performance problems allegedly caused by work motivation, work environment and work discipline that is less than PT. KAO Semarang. Purpose of this study was to determine the effect Influence of Motivation, Work Environment and Work Discipline on Employee Performance either partially or simultaneously. With the holding of this study, it can be a policy about motivation, work environment, work discipline and performance of employees so that the company's goals can be achieved with optimal.This type of research is explanatory research or explanation. The population in this study are employees of PT. KAO Semarang as many as 100 people. Engineering samples are used so that the whole population census used as a sample. Thus the sample used as many as 100 people. Methods of data collection using questionnaires, while data analysis technique used is to test the validity, reliability, t test, F test test, determination coefficient and regression analysis. Calculations in this study using SPSS 16.0 for Windows.The calculations show that: work motivation has an average value of 3.86 to be in either category, work environment has an average value of 3.66 to be in either category, variable working discipline has an average value of 3.62 so as to be in either category, there is an influence either partially or simultaneously variables of motivation, work environment and work discipline on the performance of employees of PT. KAO Semarang. Advice given is the motivation is the variable that has the most impact on the performance of employees of PT. KAO should therefore notice company employee motivation problem by maintaining and improving work motivation, work discipline is a variable that has the least effect on the performance of employees of PT. KAO thus the company should improve and increase, for other researchers, if want to do research on the performance it should use other variables in addition to the variables contained namely research work motivation, work environment and work discipline to predict performance. Other variables that are used to predict the performance of which is leadership, organizational commitment, compensation. Thus the research on this performance will be more perfect.